Global Trends of Researches on Sacral Fracture Surgery: A Bibliometric Study Based on VOSviewer. Issue 12 (15th June 2020) - Huang, Tianji; Wu, Huayong; Yang, Shengdong; Su, Bao; Tang, Ke; Quan, Zhengxue; Zhong, Weiyang; Luo, Xiaoji
Abstract : Study Design: Bibliometric analysis. Objective: This study aims to identify and summarize the articles related to sacral fracture surgery, to compare the papers from different countries and journals, to show the trends of researches on sacral fracture surgery. Summary of Background Data: In recent years, studies on sacral fracture are growing rapidly, but there were no bibliometric studies regarding sacral fracture surgery. Methods: Excel 2016 and VOSviewer were used to identify and summarize the articles from Web of Science between 1900 and 2018. Publication number, publication year, publication country, publication organization, publication source, author, sum of times cited, H-index, and journal's impact factors were recorded and analyzed. Bibliometric maps of co-citations and maps of co-occurrence of keywords are drawn. Results: A total of 611 publications were extracted. United States published most articles (227, 37.2%), both total citations (3536) and H-index (32) of United States ranked first of all the countries. The most productive organization on sacral fracture surgery is Johns Hopkins University (14). Spine (43) published the most articles on sacral fracture surgery. The latest keyword "patterns" appeared in 2017 in 5 articles. Other relatively new keywords include "proximal junctional kyphosis, " "spondylopelvic dissociation, " "fragility fracture, " "lumbopelvic fixation" that appeared in 2017 in eight, six, six, and 25 articles, respectively. Conclusion: This bibliometric study showed that there is a growing trend both in published articles related to sacral fracture surgery and relative research interest in the last 30 years. United States dominates the research regarding sacral fracture surgery. Johns Hopkins University, Johannes Gutenberg University of Mainz, and Harborview Medical Center are the best institutions related to sacral fracture surgery research. Spine, J Orthop Trauma, and Injury are the top three productive journals on sacral fracture surgery. Sacral fracture patterns, proximal junctional kyphosis, spondylopelvic dissociation, fragility fracture, and lumbopelvic fixation may be the new research hotspot in this field. Level of Evidence: 5 Abstract : This bibliometric study analyzed features of publication year, publication country, publication organization, publication source, author, cited times, and H-index of articles extracted from Web of Science. Bibliometric maps of co-citations and maps of co-occurrence of keywords were also visualized by VOSviewer, a java program.